2015
DOI: 10.1002/lt.24050
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive phenotyping of regulatory T cells after liver transplantation

Abstract: Regulatory T cells (Tregs) play an important role in controlling alloreactivity after solid organ transplantation, but they may also impair antiviral immunity. We hypothesized that the Treg frequency and the Treg phenotype are altered in hepatitis C virus (HCV)-infected recipients of liver transplantation (LT) with possible prognostic implications. Tregs from 141 individuals, including healthy individuals, LT recipients with or without persistent HCV infections, and nontransplant patients with chronic HCV, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…( 43‐47 ) Our group has previously demonstrated that Treg phenotypes such as the expression of human leukocyte antigen – DR isotope may differentiate rejection from recurrent HCV infection. ( 20 ) However, we could not study this further in this study because none of the patients experienced biopsy‐proven rejection episodes.…”
Section: Discussionmentioning
confidence: 96%
“…( 43‐47 ) Our group has previously demonstrated that Treg phenotypes such as the expression of human leukocyte antigen – DR isotope may differentiate rejection from recurrent HCV infection. ( 20 ) However, we could not study this further in this study because none of the patients experienced biopsy‐proven rejection episodes.…”
Section: Discussionmentioning
confidence: 96%
“…Furosemide has been associated with positive DAT, without haemolysis . Also, HCV infection is associated with numerous immunological diseases, although the occurrence of haemolysis is rare . Furthermore, positive DAT with negative eluate may be secondary to non‐specific adsorption of IgG in the RBCs, which is associated with liver disease .…”
Section: Discussionmentioning
confidence: 99%
“…Different classifications of Tregs are used in clinical studies based on their expression of various functional antigens ( Sakaguchi et al, 2010 ; Gronert et al, 2015 ; Ambada et al, 2017 ). In our work we identified subsets of Tregs based on their expression of CD45R0 and CD62L, as outlined by previous studies ( Sakaguchi et al, 2010 ; Gronert et al, 2015 ; Ambada et al, 2017 ). Out of the four main Treg subsets – ‘naïve’, CM, EM, and TEMRA – we found that the last two were significantly higher in the peripheral blood of migraine patients.…”
Section: Discussionmentioning
confidence: 99%
“…Tregs were characterized by the expression of CD3, CD4 and high levels of the IL-2R alpha chain (CD25high). T cell differentiation subsets were defined based on expression pattern of CD45R0 and CD62L as ‘naïve’ (N, CD45R0–CD62L+), central memory (CM, CD45R0+CD62L+), effector memory (EM, CD45R0+CD62L–), and terminally differentiated CD45RA-positive effector T-cells (TEMRA, CD45R0–CD62L–) ( Gronert et al, 2015 ; Ambada et al, 2017 ). The expression of CD39 and CD73 was evaluated in all above mentioned T-cell subsets.…”
Section: Methodsmentioning
confidence: 99%